INTERPRETASI MUHAMMAD IQBAL TENTANG ATOMISME DALAM KALAMASY'ARIYAH - Muzairi Muzairi (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2015)
According Iqbalin The Reconstruction ofReligious Thought in Islam theAsy'arie school, of thinkers, then, the world is compounded of what they calljawahir-infinitely small parts of atoms which can-not be further divided. Since the creative activity of God is ceaseless the number of the atoms cannot be finite. Fresh atoms are coming into being every moment, and the universe is therefore  constantly growing. As the Quran says: "God adds to His creation what He wills". The essence of the atom is independent of its exixtence. This means that existence is quality imposed on the atom by God.